Modification Of Renal Haemodynamics In Cyclosporine A – Induced Renal Failure Rats By Tempol - Tan, Yong Chia (2013)
Increasing evidence suggests that oxidative stress is involved in the pathogenesis of a wide range of cardiovascular diseases including hypertension and renal failure. Oxidative stress may contribute to the progression of renal diseases indirectly by aggravating hypertension or directly by inducing the glomerular damage and ischemia. The deleterious cardiovascular effects due to oxidative stress in chronic renal failure are dramatically increasing and this concept is gaining much attention. Tempol is a redox-cycling nitroxide namely superoxide dismutase (SOD) mimetic that promotes the metabolism of many reactive oxygen species (ROS) and improves nitric oxide bioavailability. SOD catalyzes the conversion of O2 - to H2O2, which converts into water by catalase reaction. The present study was undertaken to investigate the potential effect of Tempol on the renal functional and haemodynamics in Cyclosporine A-induced renal failure and L-NAME induced hypertension models. 64 male Sprague-Dawley rats were randomly divided into eight groups (n=8). Renal failure model was produced in selected groups using CsA at a dose of 25 mg/kg/day p.o. Nitric oxide (NOx) deficiency hypertensive model was created using L-NAME at a dose of 15 mg/kg/day p.o in selected groups. Conscious blood pressure was measured using tail cuff plethysmography method weekly throughout the study period. Besides that, metabolic data, renal functional parameters were studied. Moreover, pulse wave velocity and renal cortical vasoconstriction responses to noradrenaline, phenylephrine, methoxamine and angiotensin II were observed during acute study. In addition, plasma malondialdehyde, superoxide dismutase, nitric oxide and total antioxidant capacity levels were used to determine the oxidative stress.